2022
DOI: 10.1371/journal.pone.0279354
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on contributing to health research: A qualitative interview study with research participants and patient advisors

Abstract: Objectives The aims of this study were to explore individuals’ experiences of contributing to health research and to identify the types of impact that are perceived as important by participants or patient and public advisors. Specifically, research led by NMAHPP clinicians (Nursing, Midwifery, Allied health professions, Healthcare science, Psychology and Pharmacy). Methods Semi-structured one-to-one interviews were conducted with health research participants and patient or public advisors. Interviewees were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 47 publications
(66 reference statements)
1
5
0
Order By: Relevance
“…Researchers concluded that while financial incentives improved recruitment, the potential for symptom relief and the desire to help others were stronger drivers in this population of reproductive-aged women ( 12 ). This comports with other research showing that, while appreciated and inspiring, monetary compensation is unlikely to be an isolated driver of later-phase clinical trial participation ( 10 ).…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…Researchers concluded that while financial incentives improved recruitment, the potential for symptom relief and the desire to help others were stronger drivers in this population of reproductive-aged women ( 12 ). This comports with other research showing that, while appreciated and inspiring, monetary compensation is unlikely to be an isolated driver of later-phase clinical trial participation ( 10 ).…”
Section: Introductionsupporting
confidence: 81%
“…Patients commonly report dissatisfaction about the disconnect between the delivery of clinical care in the community and research and want more integration of the two ( 4 , 10 ). Mechanisms for linking the administration of clinical trials with the delivery of routine or specialty healthcare should be considered, such as educating patients about clinical trials during routine outpatient visits (while being mindful of optimal timing to not overwhelm sick patients) ( 24 , 35 ).…”
Section: Multi-pronged Recruitment Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Relevant data related to the reported impacts of research activity by NMAHPPs. This included our previous systematic review [ 26 ], qualitative interviews with healthcare managers and research-active clinicians [ 27 ] and qualitative interviews with research participants and patient advisors [ 28 ]. Additional evidence was identified using a targeted literature search limited to the period after the previous systematic review (January 2020 to October 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous work documented the types of impact that were associated with NMAHPP-led healthcare research as reported in the literature [ 26 ]. We also explored the views of healthcare managers, research-active clinicians [ 27 ] and people who had been participants or advisors for NMAHPP-led health research [ 28 ]. The current work took place in the context of a large NHS Trust that had a pre-existing research strategy for NMAHPP professions [ 29 ] and offers locally funded competitive research fellowships [ 30 ], in addition to supporting NMAHPP applications for national research funding schemes.…”
Section: Introductionmentioning
confidence: 99%